Penggunaan Majas Dalam Lirik Lagu “Remaja” Karya HIVI - Meti Amarila Lestari; Putri Annisa Nurfitriani; Septa Adistya Kusnandar Syahputri (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Songs are included in poetic literary works that continue to develop over time. The words used in it are interesting things that must be researched because of the use of beautiful and different language in general. Like one of the songs that is popular among young people, the song "Remaja" performed by the band HIVI. Therefore, the author conducts research to find out and explain the majas in the lyrics of the song "Remaja" by HIVI with a qualitative descriptive method and stylistic approach. The results showed that there were 29 majas in the form of personification, synesthesia, metaphor, hyperbole, oxymoron majas, pararima majas, and alliteration majas. This research is recommended for people who want to know more about the majas contained in the song lyrics.